Endoscopic submucosal dissection without intubation for superficial pharyngeal cancer in a post‐total laryngectomy patient. Issue 5 (19th May 2022) - Ashikari, Keiichi; Chiba, Hideyuki; Nakajima, Atsushi
Abstract : Watch a video of this article.